Preliminary Phytochemical Studies and Evaluation of Antidiabetic Activity of Roots of Cayratia trifolia (L.) Domin in Alloxan Induced Diabetic Albino Rats - Shikha Batra, Nikhil Batra and Badri Prakash Nagori (Journal of Applied Pharmaceutical Science, 2013)
The present study aims to investigate the antidiabetic activity of roots of Cayratia trifolia (L.) Domin in alloxan induced diabetic rats. Phytochemical studies showed the presence of steroids, flavonoids and alkaloids in petroleum ether, ethyl acetate and ethanol extracts, respectively. Antidiabetic activity was evaluated by observing blood glucose levels and analyzing the serum biochemical parameters after dosing the ethyl acetate extract. Blood samples were collected from overnight fasted diabetic rats on 5, 10 and 15 days of treatment to determine blood glucose levels. On day 16, blood samples were collected to estimate the biochemical parameters. In diabetic rats, both the doses (200 mg/kg and 400 mg/kg) of ethyl acetate extract were found to be significant (P
Keywords: Antidiabetic, Hypoglycemic, Cayratia trifol